Effects of swirl on intermittency characteristics in non-premixed flames - Ranga Dinesh, K. K. J.; Jenkins, Karl W.; Kirkpatrick, M. P.; Malalasekera, W. (Taylor & Francis, 2012)
Swirl effects on velocity, mixture fraction, and temperature intermittency have been analyzed for turbulent methane flames using large eddy simulation (LES). The LES solves the filtered governing equations on a structured Cartesian grid using a finite volume method, with turbulence and combustion modeling based on the localized dynamic Smagorinsky and the steady laminar flamelet models, respectively. Probability density function (PDF) distributions demonstrate a Gaussian shape closer to the centerline region of the flame and a delta function at the far radial position. However, non-Gaussian PDFs are observed for velocity and mixture fraction on the centerline in a region where center jet precession occurs. Non-Gaussian behavior is also observed for the temperature PDFs close to the centerline region of the flame. Due to the occurrence of recirculation zones, the variation from turbulent to nonturbulent flow is more rapid for the velocity than the mixture fraction and therefore indicates how rapidly turbulence affects the molecular transport in these regions of the flame